Аналіз і шляхи вирішення проблем екологічної безпеки в Україні - Палієнко, Ольга Адольфівна (НТУ "ХПІ", 2017)
В даній статті розглядаються аспекти і підходи трансформації екологічного світогляду в умовах глобалізації, проведено аналіз екологічної кризи в Україні та світі, проаналізовані наукові та статистичні дослідження стану екологічної безпеки, рівень захворювань населення України, охарактеризовані причини погіршення екологічної ситуації, з'ясовані шляхи вирішення проблеми охорони здоров'я та безпеки життєдіяльності населення, обґрунтована необхідність формування екологічної свідомості як найважливішого фактора вирішення екологічних проблем.

In this article aspects and approaches of transformation of ecological world view are examined in the conditions of globalization, the analysis of ecological crisis is conducted in Ukraine and world, scientific and statistical researches of the state of ecological safety, level of diseases of population of Ukraine, described reasons of worsening of ecological situation, are analysed, from ways of decision of problem of guard healthy and safety of vital functions of population, reasonable necessity of forming of ecological consciousness as a major factor decision ecological problem. The study of ecological safety is conditioned as a social need in the study of the spiritual foundations and social regulators of the doctrine of ecological safety of Ukraine, the need for development of which has long been overdue, and the need for practical solution to the problem. A factor that actualizes the problem is the social and spiritual need for shaping the values of the ecological consciousness as a form of social consciousness, the cultivation of an ecological world outlook as the basis of an environmentally safe society.
Analysis and ways of solving environmental safety problems in Ukraine
Keywords: екологічна безпека; загроза життя; екологічна криза; захворювання; працездатність населення; забруднення території; ecological safety; threat of life; ecological crisis; disease; capacity of population; contamination of territory